2006
DOI: 10.1016/j.ijgo.2006.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol and active management of the third stage of labor

Abstract: In situations where oxytocin and or ergometrine are not consistently and appropriately used during third stage of labor, misoprostol should be considered for inclusion in the AMTSL protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 21 publications
2
17
2
9
Order By: Relevance
“…In addition, approximately 5% of women bled ≥350 ml in secondary prevention clusters, which is lower than the 25% hypothesised based on prior studies 13. The reasons for the low levels of bleeding in this study are unclear, although other studies document low or declining measured ‘PPH rates’ during study recruitment, thought to be due to increased provider confidence and training 21, 22, 23, 24, 25. In compliance with government policy, ANMs referred high‐risk deliveries to higher‐level facilities, and women enrolled may have constituted a low‐risk population, although numerous studies have shown that it is difficult to identify the majority of women who will experience PPH based on pre‐existing risk factors.…”
Section: Discussioncontrasting
confidence: 51%
“…In addition, approximately 5% of women bled ≥350 ml in secondary prevention clusters, which is lower than the 25% hypothesised based on prior studies 13. The reasons for the low levels of bleeding in this study are unclear, although other studies document low or declining measured ‘PPH rates’ during study recruitment, thought to be due to increased provider confidence and training 21, 22, 23, 24, 25. In compliance with government policy, ANMs referred high‐risk deliveries to higher‐level facilities, and women enrolled may have constituted a low‐risk population, although numerous studies have shown that it is difficult to identify the majority of women who will experience PPH based on pre‐existing risk factors.…”
Section: Discussioncontrasting
confidence: 51%
“…The mean duration of 3rd stage of labour was also comparable in all the three groups, p = 0.115 (4.42 min oral misoprostol group, 4.420 min rectal misoprostol group, 4.158 min in IM 15methyl-PGF2α group). This was comparable to Nellore V et al study and other studies [23][24][25][26] .…”
Section: Duration Of 3 Rd State Of Laboursupporting
confidence: 91%
“…The present study revealed the superiority of rectal misoprostol regimen over intravenous oxytocin. Previously, other studies had shown similar results for oral misoprostol (15). Contrary to our findings, some studies have reported that the percentage of retained placenta and the amount of bleeding in the intervention group of oxytocin were significantly lower in the intramuscular oxytocin group (10).…”
Section: Discussioncontrasting
confidence: 52%